Unggul Accreditation as a Quality-Based Marketing Strategy to Build University Brand Image - Hawwin Muzakki; Khoirul Mudawinun Nisa’ (Badan Usaha Milik Desa Berkaho Pungpungan, 2025)
Abstract. This study aims to examine the implementation of unggul accreditation as a brand image strategy to enhance the competitive advantage of higher education institutions. Focusing on the Early Childhood Islamic Education (PIAUD) Study Program at UIN Sayyid Ali Rahmatullah Tulungagung, this research explores how quality-based marketing strategies—through planning, brand-building factors, and positioning—contribute to institutional reputation and student trust. Using a qualitative field research approach, data were collected through interviews, observations, and documentation. The results show that unggul accreditation serves not only as a quality assurance label but also as a key branding component that differentiates the program from its competitors. Key success factors include the formation of an accreditation team, strong curriculum design, excellent infrastructure, and a commitment to continuous improvement. Strategies employed include clear positioning, effective differentiation, and integrated branding efforts that leverage institutional excellence, brand association, and uniqueness.